ANALISIS PENGARUH HARGA CRUDE PALM OIL DAN NILAI TUKAR USD/IDR TERHADAP RETURN SAHAM PT BAKRIE SUMATERA PLANTATIONS, TBK - , Kanya Budianing Pratiwi; , Anis Barid.,*", Orr. M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Coconut palm is one of the main commodities in the agribusiness sector. There are some refined palm products such as Crude Palm Oil (CPO). Indonesia being the largest CPO producer and compete with Malaysia. In the face of international trade, risk of changes in currency exchange rates is a matter that must be considered. Rise and fall of corporate profits may be affected by the CPO price changes and changes in currency exchange rates. This study wanted to see the impact of CPO prices and the exchange rate of USD/IDR to return of PT Bakrie Sumatera Plantations, Tbk. The time span was divided into two period which is period A and period B. Period A is the period before the subprime mortgage crisis (2006-2007)and Period B is the periode which the crisis begin (2008-2009). This research uses multiple regression analysis with SPSS software 17.00 version. The amount of research data as much as 351 in period A and 359 in the period B. The results with statistical t test showed that the CPO price has no effect on either the stock return in period A and in the period B. Other variable is the exchange rate of USD / IDR has a significant influence on stock return in period A but has no effect on the period B.